THE EFFECT OF FINANCIAL PERFORMANCE ON THE RISK OF BANKRUPTCY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA (USING THE MODIFIED ALTMAN Z-SCORE METHOD FOR THE PERIOD 2011-2017) - Afiqoh, Luluk; Laila, Nisful (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2018)
This research aims to find out the influence of financial performance measured using the Capital Adequacy Ratio variable, Financing to Deposit Ratio, Leverage, Bank Size, Loan to Asset Ratio and Return on Assets to the risk of sharia bank bankruptcy in Indonesia calculated using the Altman Z-Score method Modification. This study uses a quantitative approach with panel data regression analysis techniques. The results of this study show partially the variable Capital Adequacy Ratio, Financing to Deposit Ratio, Bank Size has a significant positive effect, the variable Loan to Asset Ratio Leverage has a significant negative effect, and Return on Asset has a positive and insignificant effect. Nevertheles the variable Capital Adequacy Ratio, Financing to Deposit Ratio, Leverage, Bank Size, Loan to Asset Ratio and Return on Asset have a significant effect on the value of Altman Z-Score as a measure of the risk of bankruptcy in Islamic commercial banks in Indonesia.Keywords: Financial Performance, Islamic Commercial Bank, Risk of Bankruptcy, Altman Z-Score Modification